A case of hereditary hemorrhagic telangiectasia presenting with brain abscess - Marwa Zeyad; Basel Musmar; Mohammad Alnees; Malik Ghannam; Qusay Abdoh (Brain Disorders, 2023)
Background: Hereditary hemorrhagic telangiectasia (HHT), characterized by telangiectases and arteriovenous malformations that can occur in any organ but primarily the lungs, liver, and brain, is an autosomal dominant disorder. Brain abscess, though a rare and potentially fatal complication, can be an initial presentation of this condition. Case summary: A 60-year-old man presented with anemia and black tarry stools, then developed right-sided weakness initially misdiagnosed as an ischemic stroke. Subsequent onset of headaches and high-grade fever led to the diagnosis of brain abscess, and HHT was subsequently identified. Conclusion: This case underscores that brain abscess can be an initial symptom of HHT. Prompt diagnosis and treatment are vital, which requires physicians to maintain a high index of suspicion and conduct appropriate investigations promptly.